The Right to Immediate Preservation: Addressing Legal Barriers Due to Death Investigation - Andrew T. McKenzie; Alicia Keberle; Francesca Minerva; Ariel Zeleznikow-Johnston; Jason Harrow (Forensic Sciences, 2025)
Contemporary human preservation technologies aim to preserve the structure of the body—and especially the brain—after legal death. Although it has not yet been demonstrated, some believe that this may act as a bridge to future medical technologies that could allow for the recovery of life, if this ever becomes feasible and humane. However, current death investigation practices impose two significant obstacles to high-quality preservation. The first and most common is ischemic delay—the period between legal death and initiation of preservation while the death is investigated, during which brain tissue progressively degrades. The second is involuntary autopsy, where tissue disruption can severely compromise preservation quality. Through analysis of legal precedents and the ethical principles of bodily autonomy, non-discrimination, and potential preservation of life, we argue that individuals should be allowed a way to prevent both ischemic delay and autopsy from affecting the quality of their preservation. We explore potential avenues to implement a right to immediate preservation, including administrative, legislative, and judicial approaches, aimed at balancing this right with the societal interest in performing death investigations. This narrative review has implications for individual autonomy, public policy, and the legal framework surrounding death investigation in the context of emerging preservation technologies.